The Problem of Twelve: When a Few Financial Institutions Control Everything - Posner, Eric A. (Journal of Economic Literature, 2024)
Eric A. Posner of University of Chicago reviews “The Problem of Twelve: When a Few Financial Institutions Control Everything” by John Coates. The Econlit abstract of this book begins: “Explores issues that arise when a small number of actors acquire the means to exert outsized influence over the politics and economy of a nation, focusing in particular on the two late-twentieth-century institutions of index funds and private equity funds.”